Spatial wave structure created by wind input - Adcock, T; Taylor, P (2008)
Waves on the open sea grow under the influence of strong winds. However, most wave models used in offshore engineering neglect any energy input or dissipation. A study on the possible effects of energy transferred from the wind on the nonlinear dynamics of steep wave groups was carried out. In a uni-directional approximation, solitary wave structures were preferentially amplified due to their inherent local balance between dispersion and nonlinearity. In contrast, in a directional spread approximation, there were no isolated solitary wave groups. Energy input could lead to the creation of a locally close to unidirectional three sisters event, followed by the spread of large geometric structure across the entire computational domain. This is an abstract of a paper presented at the 18th International Offshore and Polar Engineering Conference (Vancouver, BC, Canada, 7/6-11/2008).